Voyage into collective memory : marginality in Italian ethnographic documentaries of the 50’s - Borjan, Etami (2008)
In the 50’s in Italy there was a renewed anthropological and intellectual interest in the South which resulted in a new way of relating to both fictional and documentary reality. The studies of the most prominent Italian anthropologist Ernesto De Martino brought out diversity points in the contemporary history of the country that was still struggling to build a sense of national unity and identity among its culturally, linguistically, traditionally and historically disunited inhabitants, thus revealing how much unknown was the South that had its own history and social practices governed by the non-written natural laws of a thousands of years old survival system. Between 1959 and 1961 De Martino was cooperating in the making of documentary films mostly with Nino Dal Fra, Cecilia Mangini and Gianfranco Mignozzi, directors who portrayed traditional habits and costumes of the South.